Desinformação e jornalismo: as estratégias de verificação da agência Lupa durante as eleições presidenciais brasileiras de 2018 - Lauriano, João Victor Mariano Barbosa Inácio (2020)
Through an analysis of the content produced by Agência Lupa, a study of how journalism can expand and qualify its activities is carried out here by developing fact-checking projects with the aim of identifying and avoiding the consumption of false content distributed over the network. . The research focuses on the Brazilian electoral period of 2018 and presents the “factual truth” as facing disinformation. Theoretically, this work covers studies on network society and journalism, in the context of fake news and post-truth, in addition to strategies to combat disinformation in the electoral period, as well as the impact of these elements in the construction and consolidation of democracy and citizenship. contemporary. The methodological approach used is exploratory research, whose reliability is anchored in the application of Content Analysis employed in 408 journalistic contents referring to the verification of information produced and shared on a network by the Agência Lupa, collected during the months of July to October 2018. The results show, then, that the “factual truth” is reinforced in the political coverage practiced by Lupa through the presentation of the origin of the sources used in the checks, as well as the exposure of the method used to develop each verification, reinforcing the role of journalism in maintenance of democratic practices through political oversight.